2005
DOI: 10.1002/ajpa.20354
|View full text |Cite
|
Sign up to set email alerts
|

Federal Repatriation Legislation and the Role of Physical Anthropology in Repatriation

Abstract: Two laws governing the disposition of Native American human remains in museums and institutions have had a profound impact on anthropology, and especially physical anthropology. In contrast to the perception of constant conflict between Native Americans and physical anthropologists, the repatriation process based on these laws has been in large part harmonious between institutions and Native peoples in the US. Despite misconceptions, the Native American Graves Protection and Repatriation Act (NAPGRA; 25 United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 55 publications
0
37
0
2
Order By: Relevance
“…Hrdlicka never tested these assumptions. Ousley et al (2005) confirmed their biological ancestry by applying a discriminant function analysis on the Karluk sample and compared them to other known East Asian groups (Chinese and Japanese) and Native Alaskan samples. These authors found the majority of Kodiak Island individuals (95%) clustered closest to other Chinese and Japanese rather than Native Alaskan individuals.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Hrdlicka never tested these assumptions. Ousley et al (2005) confirmed their biological ancestry by applying a discriminant function analysis on the Karluk sample and compared them to other known East Asian groups (Chinese and Japanese) and Native Alaskan samples. These authors found the majority of Kodiak Island individuals (95%) clustered closest to other Chinese and Japanese rather than Native Alaskan individuals.…”
Section: Methodsmentioning
confidence: 95%
“…The cemetery dates from 1885 to 1923 according to historical records and artifacts recovered with the burials (Owsley et al, 1997;Schmidt, 2006). These skeletal remains are currently being stored at the (Jones, 1931;Ousley et al, 2005). The amateur archaeologist assumed these individuals to be Chinese based on the presence of a 'pig tail' on one of the men (Jones, 1931).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal remains also provide insights into adaptive successes in response to new environmental stresses. While the authenticity and reliability of historical documents and other cultural artifacts may be dubious, skeletal analyses offer an objective, independent source of information that is less subject to cultural manipulation and historical revision [3].…”
Section: The Value Of Studying Human Remains and Increasing Studies Omentioning
confidence: 99%
“…Human Skeletal Remains (1994) (Ousley et al 2005). Buikstra and Ubelaker devised their approach to the collection of skeletal data in response to the need to develop a standardized data collection protocol that would satisfy the needs of archaeologists, biological anthropologists, researchers, and descendent aboriginal groups involved with NAGPRA and the repatriation process for standardized, comprehensive and directly comparable data.…”
Section: In Standards For Data Collection Frommentioning
confidence: 99%